GOVERNANCE AND STAKEHOLDER INVOLVEMENT IN THE DUTCH PENSION INDUSTRY, LESSONS FOR DEVELOPING COUNTRIES. (October 2014) - de Kruijf, Johan A. M.; de Vries, Michiel S.; Collins, Paul D.; Podger, Andrew; Dong, Keyong
SUMMARY The article discusses governance structure and stakeholder involvement in pension plan reforms. Although the global financial crisis has put pressure on pension reforms, some reforms were implemented earlier because of sustainability issues that had emerged on the basis of, among other issues, demographic trends. We show, based on Dutch experiences, that stakeholders and individual participants in particular were only partially involved in these changes. On the basis of these findings, we propose some tools to improve stakeholder involvement, which can contribute to sustainable support from stakeholders to pension plans. Copyright © 2014 John Wiley & Sons, Ltd.